Observational study on the utilization pattern of adjuvant anti-epileptics and their adverse effects - Rangarajan, Punitha; Moorthy, Kulandaiammal; Subbiah, Arunan (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Epilepsy is a disease characterized by an enduring predisposition to generate epileptic seizures. Pharmacological therapy is the cornerstone of treatment of epilepsy. In more than 50% patients seizure not controlled with first-line anti-epileptic drugs so added with adjuvant drugs. Therefore adjuvant anti-epileptic drugs play an important role in preventing seizure remission in known epilepsy patients. Observational study was to evaluate the utilisation pattern of adjuvant anti-epileptic drugs and to assess their clinical correlation and observe the adverse effects of the adjuvant anti-epileptics. Methods: Eligible 100 patients who attended the neurology outpatient department where enrolled in the study. Demographic data, type of epilepsy, presence or absence of seizure episode (4 months), adjuvant anti-epileptic prescribed along with the first-line drugs and adverse effects were noted. Clinical correlation and rationale for the usage of adjuvant anti-epileptics were assessed. Descriptive statistics used for statistical analysis. Results: The most common types of seizures were generalised tonic clonic seizures (41%) and complex partial seizures (37%). Most commonly used 1st line drug was phenytoin tablet. Most common adjuvant anti-epileptics used were clonazepam (30), clobazam (24) tablets. Most common adverse effect noted was dizziness (31%). Conclusions: Tablet clonazepam is effective adjunct for tonic clonic seizures. Clobazam table is recommended as add-on drug for focal and generalised seizures. Adjuvant anti-epileptic drugs decrease seizure remission with fewer tolerable adverse effects.